"Condoms Are Boring": Navigating Relationship Dynamics, Gendered Power, and Motivations for Condomless Sex Amongst Adolescents and Young People in South Africa. Issue 1 (2nd January 2021) - Duby, Zoe; Jonas, Kim; McClinton Appollis, Tracy; Maruping, Kealeboga; Dietrich, Janan; Mathews, Catherine
Abstract: Condoms remain an important method for preventing HIV prevention and unintentional pregnancies, however their use in South Africa is sub-optimal. We analyzed survey data on reported condom use among 3009 sexually active adolescent girls and young women (AGYW) aged 15–24 years, and qualitative data from interviews and focus group discussions with 237 AGYW and 38 male peers. Our findings describe the current condom use landscape among adolescents and young people in South Africa, illustrating relationship dynamics, gendered power and notions of masculinity which influence condom negotiation and use in young heterosexual South Africans' sexual encounters.